Origin of low frequency inductive impedance loops of O2 reduction reaction of solid oxide fuel cells - Chen, Kongfa; Ai, Na; Jiang, San Ping (Elsevier BV * North-Holland, 2016)
Inductive impedance loop at low frequencies on electrochemical impedance spectroscopy curves is a common phenomenon in electrochemical reactions such as fuel cells. Here, we study the occurrence of low frequency inductive impedance loops and their evolution for the oxygen reduction reaction on Gd0.2Ce0.8O1.9 infiltrated La0.8Sr0.2MnO3 (GDC-LSM), GDC infiltrated Pt (GDC-Pt) and mixed ionic and electronic conducting (MIEC) La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) cathodes under solid oxide fuel cells (SOFCs) operation conditions. The incorporation of GDC nanoparticles (NPs) substantially enhances the electrochemical activity of LSM and Pt electrodes with the concomitant occurrence of an inductive impedance loop at low frequencies. However, the low frequency impedance loop disappears for the GDC-LSM with GDC NPs larger than 41 nm or after polarization at 200 mA cm− 2 for more than 60 min. In the case of LSCF electrode the low frequency inductive loop transfers to capacitive arc after polarization for 30 min. The occurrence of low frequency inductive loops is closely related to the electrode electrocatalytic activity and microstructure and is primarily determined by the ability of the electrode materials to supply atomic oxygen for the reaction at the interface. A mechanism of competitive atomic oxygen supply and dissociative oxygen adsorption and diffusion is proposed for the occurrence of the inductive loops at low frequencies for the O2 reduction reaction of SOFCs.